Multi-loop control system design: a game theoretical approach for computer-controlled systems - Gambier, Adrián; Wellenreuther, Andrea; Badreddin, Essameddin (46th IEEE Conference on Decision and Control, 2007, 2007)
In this contribution, previous work for the design of multi-loop control systems with several controllers is extended in several directions. The main idea is to model the whole control system as a cooperative dynamic game, where controllers are the players. The solution of this game is obtained by using multiobjective optimization (MOO). The extensions considered in this paper are the following: First, the problem is formulated in a discrete-time framework so that digital control systems will be able to be designed in a natural way. Moreover, the choice of objective functions and control laws are discussed in details. Finally, a more complex (compared with the previous work) simulation example illustrates the advantage of using the method.
Gesehen am 05.07.2019